ANTIOXIDANT ACTIVITY EVALUATION OF KALANCHOE PINNATA (LAM.) PERS. FRESH LEAF JUICE - BHAVSAR, SHRUTI; CHANDEL, DIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this study was to determine the antioxidant and free radical scavenging properties of Kalanchoe pinnata (Lam.) Pers. fresh leaf juice for standardized doses using different types of assays. Methods: The investigation of the antioxidant activity was carried out for the previously standardized doses (by cytotoxicity and genotoxicity analysis) – 50 μl (low dose - LD) and 70 μl (high dose-HD) by Phosphomolybdenum (PM), Ferric Reducing Antioxidant Power (FRAP), 2, 2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging activity, and 2, 2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity assays. Results: The activity measured by PM assay for LD and HD of the extract was equivalent to 109 μg/ml and 141 μg/ml of ascorbic acid, respectively, while by FRAP assay, it was equivalent to 17.5 μg/ml and 47 μg/ml of ascorbic acid, respectively. The activity measured by DPPH assay was found equivalent to 83 μg/ml and 177.5 μg/ml of ascorbic acid for LD and HD, with the percent scavenging activity 4.55% and 17.04%, respectively. Similarly, the activity of LD and HD by ABTS assay was found equivalent to 277.5 μg/ml and 308 μg/ml of ascorbic acid with the percent scavenging activity 39.01% and 47.93%, respectively. Conclusion: The changes observed in the absorbance values for all the assays reflected the increasing antioxidant activity of the plant extract in dose-dependent manner, which justifies the traditional use of this herb in prevention of diseases induced by oxidative stress. The antioxidant activity of K. pinnata fresh leaf juice has been conducted for the 1st time and has not been previously reported.